TEACHERS' WRITTEN FEEDBACK TO EIGHTH GRADERS' RECOUNT TEXTS IN A JUNIOR SECONDARY SCHOOL IN CIANJUR - Nisa, Nabila Nurin (2016)
This paper, entitled Teachers' Written Feedback to Eighth Graders' Recount Texts in A Junior Secondary School in Cianjur. The aims of the research was to reveal the extent of the teachers' feedback on students' recount texts that enhances the students' writing performances. It employed a descriptive case study, involving two English teachers in Cianjur who taught thirty students per each teacher. The data were gathered from document collection and interview. The obtained data were mainly analyzed based on Ellis (2009), Ferris (2006) and Matsumura et al. (2002) explaining strategies in providing feedback and categories of feedback. The findings showed that teachers' written feedback enhances students' writing performances in term of grammar, the enhancement was influenced by teachers' direct and indirect feedback. In direct feedback, students understand the errors, know the correct forms and immediately correct their errors. Whereas, in indirect feedback, students are empowered, so that, they are able to correct their own mistakes, because it engages them in a more thoughtful form of language improvements. Students also responded positively in being given feedback since feedback helped them to perform better in the next writing. However, for the sake of clarity and understanding, it is also important for teachers to consider their further strategies in providing feedback.;--- Penelitian ini berjudul Umpan Balik Tertulis Guru pada Teks Recount Siswa Kelas Delapan di Sebuah Sekolah Menengah Pertama di Cianjur. Tujuan penelitian ini adalah untuk mengetahui sejauh mana umpan balik guru pada teks recount siswa dapat meningkatkan keterampilan menulis siswa. Penelitian ini menggunakan studi kasus deskriptif, melibatkan dua guru bahasa Inggris di Cianjur yang masing-masing mengajar tiga puluh orang siswa. Data-data yang ada dikumpulkan dari metode pengumpulan dokumen dan wawancara. Data yang diperoleh sebagian besar dianalisis berdasarkan Ellis (2009), Ferris (2006) dan Matsumura dkk (2002) yang menjelaskan strategi dalam pemberian umpan balik dan kategori umpan balik. Hasil dari penelitian ini menunjukan bahwa umpan balik tertulis guru dapat meningkatkan keterampilan menulis siswa dalam hal tata bahasa, peningkatan keterampilan menulis siswa di pengaruhi oleh umpan balik guru secara langsung dan umpan balik guru secara tidak langsung. Pada umpan balik langsung, para siswa dapat memahami kesalahan-kesalahan mereka, mengetahui bentuk penulisan yang benar dan dapat langsung memperbaiki kesalahan mereka. Sedangkan pada umpan balik tidak langsung, para siswa lebih terdorong, sehingga siswa dapat memperbaiki kesalahan mereka oleh diri mereka sendiri, karena hal itu memacu siswa untuk memiliki perkembangan bahasa yang lebih baik. Para siswa juga menanggapi pemberian umpan balik secara positif, karena umpan balik membantu mereka untuk dapat membuat tulisan-tulisan yang lebih baik. Tetapi, demi kejelasan dan pemahaman, ini juga penting bagi guru-guru untuk mempertimbangkan strategi lain dalam pemberian umpan balik.